A CASE REPORT ON MANAGEMENT OF SHEETAPITTA WITH KHADHIRADHIYOGA W.S.R TO CHRONIC URTICARIA (AYUSHDHARA, 2019)
Sheetapitta is a Vatapradhana Tridoshajavyadhi with the involvement of Dushyasrasa, Rakta. It is characterized by Lakshanas like Varatee Damstravathshotha (wheals), Kandu, Jwara, Chardhi, Vidaha and Toda for more than 6 weeks. This disease disturbs the daily activities of an individual and makes him dependent and depressed. In present study Khadiradhiyoga has given to patient, it contains Khadirarista, Haridrakhanda, Manasamitravataka Khadira.Objective of the study: To observe the effect of Khadiradhiyogaa combination of (Khadirarista, Haridrakhanda, Manasamitravataka) internally in the management of Sheetapitta and to withdraw from allopathic medicine Cetirizine hydrochloride and to maintain the patient on Ayurvedic medication, to prevent recurrences, avoidance of precipitating factors, management of underlying disease.Methods: A 23 yrs male patient presented with complaints of severe itching all over the body since 3 years, used several allopathic medications, only cetirizine tablet has given to the patient and got temporary relief, itching increasing when patient is having mental stress, severe hives while itching, reddish discolouration and severe headache during the episodes. In present study we have given Khadiradhiyoga (Khadirarista, Haridrakhanda, Manasamitravataka) for 3 months with help of assessment tools and gradation of symptoms, the findings of research work were analyzed.Results: Results of this study shows that complete relief from the symptoms like, fever, headache, depression, itching, multiple macular erythematous lesions and the count of AEC, ESR, Transaminases and lipid profile has been reduced.